(untitled) (CIPEEX, 2025)
Introduction: This study is part of an integrative review of the literature examining the impact of palliative care work on the mental health of healthcare professionals. Healthcare professionals working with palliative care patients are constantly exposed to the fragility of life and the suffering of others, which can take a toll on their mental health. Understanding the occupational and psychological aspects associated with these workers’ trajectory, as well as intervention strategies that can be implemented, is essential. Objectives: Investigate the psychological consequences of working in palliative care for healthcare professionals and analyze possible intervention strategies. Methods: This integrative literature review aims to answer the guiding question: "What are the impacts of working in palliative care on the mental health of healthcare professionals?" Searches were conducted in the BVS database using the health science descriptors "occupational stress," "health professionals," and "palliative care." Five original articles published between 2020 and 2025 were selected. Results: Of the eight evaluated stressors, chronic stress resulting from the accumulated burden of end-of-life care management was found to be the primary predictor of mental health issues over time. The analyses revealed two primary mental health trajectories in response to chronic stress: resilience and persistent distress. Resilient professionals benefit from the positive emotions generated from helping patients, which provide gratification and motivation. However, excessive empathy in contexts of chronic stress becomes a vulnerability that contributes to distress trajectories, despite being essential for compassionate care. The mental health of professionals is impacted by specific characteristics of palliative care work: superficial performance is associated with increased compassion fatigue and reduced perception of overall health, while resources such as emotional self-efficacy and perception of meaningful work promote better overall health and reduce fatigue, favoring resilience. Self-care and self-awareness were identified as predictors of coping with death, with self-compassion being the factor with the greatest predictive power. Additionally, quality of professional life positively affected personal well-being. Recent evidence indicates that psychological and physical fatigue is present in both home-based and inpatient palliative care settings. Concurrently, psychological mechanisms are crucial for healthcare professionals in palliative care to cope with stress, and interventions focusing on self-compassion, psychological flexibility, cognitive empathy, and professional training have been effective in preventing and managing compassion fatigue. These interventions also facilitate the identification of potentially traumatic situations. Conclusions: Healthcare workers in palliative care are prone to experiencing chronic stress, compassion fatigue, emotional exhaustion, a reduced perception of their overall health, and emotional vulnerability. Therefore, it is necessary to implement intervention strategies that highlight the rewarding aspects of care, such as the gratification and motivation generated by helping patients. Additionally, raising awareness of the occupational and psychological resources necessary for coping with the profession can improve the quality of life of these professionals.